Gormenghast - Peake, Mervyn, 1911-1968 (Gormenghast trilogy, 2007)
Titus Groan is seven, Lord and heir to the crumbling castle Gormenghast. A gothic labyrinth of roofs and turrets, cloisters and corridors, stairwells and dungeons, it is also the cobwebbed kingdom of Byzantine government and age-old rituals, a world primed to implode beneath the weight of centuries of intrigue, treachery, and death. Steerpike, who began his climb across the roofs when Titus was born, is now ascending the spiral staircase to the heart of the castle, and in his wake lie imprisonment, manipulation, and murder.